Isradipine Loaded Solid Lipid Microparticles for improved Oral Drug Delivery: preparation, solid state characterization and pharmacokinetic evaluation - PALANISAMY VISHNU (Journal of Global Pharma Technology, 2019)
Purpose: The objective of the study was to develop and evaluate the isradipine (ID) loaded solid lipid microparticles (SLMs) for enhanced oral delivery. ID is a dihydropyridine calcium channel blocker, having low oral bio-availability (15-24%) due to poor aqueous solubility and also hepatic first-pass metabolism.Methods: ID-SLMs were developed by hot homogenization coupled with ultrasonication method followed by lyophilized. The prepared SLMs were optimized. Solid state characterization and surface morphology of SLMs were analyzed using FTIR, DSC, XRD and SEM, respectively. The physical stability of optimized formulation was studied at refrigerated and room temperature for 6 months. Further, single dose oral bioavailability study was conducted in male Wistar rats compared to suspension at a dose of 5 mg/kg body weight.Results: ID-SLMs prepared with Dynasan-114 (ID8) having particle size, PDI, ZP and entrapment efficiency (EE) of 618.2±4.01 nm, 0.408±0.020, -25.9 mV and 94.85±3.61%, respectively and was physically stable for 6 months. Formulation ID8 SLM showed faster release, has less particle size and more zeta potential. FTIR and DSC, XRD studies revealed that no interaction between the drug and lipids, and conversion of drug to amorphous form. SEM studies showed nearly spherical shaped particles. From in vivo studies, indicated that 2.69-folds enhancement in the bioavailability of SLM compared with control.Conclusion: Thus, the results conclusively demonstrated the role of SLMs for significant enhancement in vivo effect of ID.